Avalanche survival depends on the time of day of the accident: A retrospective observational study. (May 2022) - Rauch, Simon; Koppenberg, Joachim; Josi, Dario; Meuli, Lorenz; Strapazzon, Giacomo; Pasquier, Mathieu; Albrecht, Roland; Brugger, Hermann; Zweifel, Benjamin; Pietsch, Urs
Abstract: Introduction: We aimed to investigate the relationship between the time of the day and the probability of survival of completely buried avalanche victims. We explored the frequency of avalanche burials occurring after sunset, and described victims' characteristics, duration of burial and rescue circumstances compared to daytime avalanches. Methods: In this retrospective, observational study, we analysed avalanche data from the registry of the Swiss Institute for Snow and Avalanche Research, from 1998 to 2020. Results: A total of 3892 avalanche victims were included in the analysis, with 72 of the accidents (1.85%) occurring in the nighttime. Nearly 50% of the victims involved in nighttime avalanche accidents were completely buried, compared to about 25% of victims in daytime avalanches. Completely buried victims were rescued by a companion less often at night than in the daytime (15% vs. 51%, p <.001). The search and rescue of completely buried avalanche victims took longer during the nighttime compared to the daytime (median 89 min vs 20 min, p =.002). The probability of survival decreased as the day progressed; it was highest at around midday (63.0%), but decreased at sunset (40.4%) and was the lowest at midnight (28.7%). Conclusions: Avalanche accidents at night are a rare event, and probability of survival after complete burial is lower during the nighttime compared to the daytime. The most relevant reason for this is the longer duration of burial, which is explained in part by the lower rate of companion rescue and the lower rate of victim localisation with an avalanche transceiver.